Effects of root colonization by zinc-solubilizing bacteria on rice plant (Oryza sativa MR219) growth - Othman, Nur Maizatul Idayu; Othman, Radziah; Saud, Halimi Mohd; Wahab, Puteri Edaroyati Megat (Agriculture and Natural Resources, 2017)
Two experiments were conducted using gnotobiotic conditions and sand culture treatment to determine the effects of root colonization by zinc -solubilizing bacteria (ZSB) on rice growth. Both experiments were designed as complete randomized designs. The first experiment was conducted in a growth chamber under gnobiotic conditions. Five-day-old rice plantlets (MR219) were inoculated with bacterial isolatesd-Acinetobacter sp. (TM56) and Serratia sp. (TM9). The roots were cut for analysis using scanning electron microscopy and transmission electron microscopy. The second experiment was also conducted in a growth chamber under sand culture conditions. The treatments consisted of the control, two bacterial isolates-Acinetobacter sp (TM56) and Serratia sp. (TM9), two types of zinc sources-ZnSO4 and ZnO and three zinc rates-0 mg/L, 0.2 mg/L and 0.4 mg/L. Data were subjected to analysis of variance and means comparison. Acinetobacter sp. and Serratia sp. were able to colonize and penetrate rice plant roots. Bacterial populations of Serratia sp. were affected by different rates of zinc for endophytes and the rhizosphere. From the study, there were significant differences among bacterial inoculation and the different rates and sources of zinc. However, inoculation with Acinetobacter sp. at 0.2 mg/L of ZnSO4 produced the highest rice plant growth and root development. It was concluded that rice plant growth was affected by ZSB inoculation, zinc sources and the rate of zinc.